Borane Catalyzed Redox Isomerization of 2‐Amino Chalcones: Hydride Abstraction or Hydride Migration?. Issue 46 (21st September 2021) - Zhou, Rundong; Paradies, Jan
Abstract: The borane catalyzed redox isomerization of 2‐amino chalcones was developed. The tetrahydroquinolines are obtained in high yield as a mixture of cis / trans diastereomers in a ratio of 2 : 1 to >95 : 5. The reaction mechanism is investigated by mechanistic, kinetic, and computational methods, concluding that the reaction proceeds through concerted [1, 5] hydride shift in contrast to borane‐mediated C(sp 3 )−H hydride abstraction. Abstract : The borane catalyzed redox isomerization of 2‐amino chalocones was developed. Mechanistic investigations by kinetic, isotopic labelling, and competition experiments as well as computational studies corroborate the concerted [1, 5] hydride shift as operative mechanism. The redox isomerization products are obtained in high yield and up to >95 : 5 diastereoselectivity.